Interviewing Javier Elzo. (Journal of Parents and Teachers, 2014)
This article interviews Javier Elzo, an important sociologist in Spain who says that young people consume alcohol in an intense way. Explain that the bottle does not require an increase in alcohol consumption, debate about lengthening the age of onset of alcohol consumption, the importance of family and teacher performance and the path to happiness.
Keywords: Interview; sociology; alcohol; bottle; legal age to consume alcoholic beverages; unhappiness.